Associations between Sleep-Disordered Breathing and Metabolic Risk Factors beyond Obesity - Yusuke Wakabayashi; Rie Oka; Masako Nakaya; Shigehiro Karashima; Mitsuhiro Kometani; Masaru Sakurai; Kenichi Yoshimura; Takashi Yoneda (Journal of Diabetes Research)
Objective. Individuals with multiple metabolic risk factors often experience concomitant sleep-disordered breathing (SDB). We aimed to determine the associations of SDB with individual components of metabolic syndrome independent of obesity. Methods. A cross-sectional study was conducted in 1137 employees aged 30–64 years. Apnea-hypopnea index (AHI) was assessed using a portable monitor for obstructive sleep apnea by admission. Of these, 451 participants took an oral glucose tolerance test to assess homeostatic model assessment of insulin resistance (HOMA-IR) and Matsuda insulin sensitivity index (ISI). Results. The odds ratio (OR) of the highest category of the AHI (≥15 episodes per hour) compared to the lowest one (<5 episodes per hour) was significantly elevated for hypertension, for hypertriglyceridemia, and for low HDL-cholesterolemia when adjusted for age, sex, and alcohol and smoking status (p<0.05). After further adjustment for body mass index (BMI) or waist circumference, the associations for hypertension still remained statistically significant (p<0.05) while those for hypertriglyceridemia and low HDL-cholesterolemia were no longer significant. The association between higher insulin resistance as assessed by HOMA-IR and Matsuda ISI and higher categories of the AHI was also lost after adjustment for BMI. Conclusion. Obesity was a strong confounding factor in the association between SDB and most metabolic risk factors including insulin resistance, except for hypertension. Further longitudinal study is needed to examine the temporal or causal relationships between SDB and metabolic risk factors. This trial is registered with UMIN-CTR UMIN000028067.